2011
DOI: 10.1177/1359104511421101
|View full text |Cite
|
Sign up to set email alerts
|

Do we miss depressive disorders and suicidal behaviours in clinical practice?

Abstract: This study involved a detailed standardized initial research assessment which was carried out with 100 young people aged 12-15 years newly referred to a child and adolescent mental health service. The assessment involved the K-SADS interview with the young person and their parent, the Strengths and Difficulties Questionnaire, the Clinical Global Impression Scale, and the Children's Global Assessment Scale. Diagnoses resulting from these 'research assessments' were compared with clinical diagnoses, which were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…39 However, it is quite likely that the most severe forms (attempted suicides and severe suicidal ideation) are most likely to be recorded by clinicians. Also, in using a self-controlled design, we decrease the chance of misclassifying controls.…”
Section: Main Strength and Limitationsmentioning
confidence: 99%
“…39 However, it is quite likely that the most severe forms (attempted suicides and severe suicidal ideation) are most likely to be recorded by clinicians. Also, in using a self-controlled design, we decrease the chance of misclassifying controls.…”
Section: Main Strength and Limitationsmentioning
confidence: 99%
“…In this study, seven young people were reported by clinicians to have depression, all of whom met diagnostic criteria on the K‐SADS as did 17 others; no young people were reported as depressed only by clinicians. Both suicidal ideation and suicidal acts were much more commonly reported by young people according to the SDA alone (22% and 19%, respectively) compared to both SDA and clinicians (6% and 6%) or clinicians alone (3%, 1%; Fitzpatrick et al., ). It is notable that 87% of the young people presenting to CAMHS in sample reached research diagnostic criteria.…”
Section: Resultsmentioning
confidence: 97%
“…Fitzpatrick et al. () focused their paper on depressive disorder, but it was unclear whether the CAMHS team under study specialised in depression. All the other work addressed the broad spectrum of mental health problems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations